Pathological and Prognostic Characterization of Craniopharyngioma Based on the Expression of TrkA, β-Catenin, Cell Cycle Markers, and BRAF V600E Mutation - Xu, Cheng; Ge, Songhan; Cheng, Juanxian; Gao, Huabin; Zhang, Fenfen; Han, Anjia (Frontiers in Endocrinology, 2022)
We collected 61 craniopharyngioma (CP) specimens to investigate the expression TrkA, β-catenin, BRAF gene mutation, and NTRK1 fusion in CP. There were 37 males and 24 females with a median age of 34 years (range 4-75 years). Histologically, there were 47 cases of adamantinomatous craniopharyngioma (ACP) and 14 cases of papillary craniopharyngioma (PCP). By immunohistochemistry, we found that moderate/high TrkA expression was detected in 47% (28/60) CP, and was significantly higher in adult patients (P = 0.018). Interestingly, TrkA is more expressed in "whorled epithelium" cells in ACP, similar to the localization of abnormal β-catenin. The abnormal expression rate of β-catenin was 70% (43/61) and the medium/high Cyclin D1 expression rate was 73% (44/60), both of which were significantly higher in ACP than in PCP. 41% (21/51) of CP had a moderate/strong P16 positive signal. 58% (34/59) of CP showed a high Ki-67 expression, and there was a significant correlation between high Ki-67 L.I. and high tumor recurrence (p = 0.021). NTRK1 fusion was not found in CP by FISH. By PCR, 26% (15/58) CP showed BRAF V600E gene mutation which mainly in PCP (100%, 14/14) except one case of ACP. Moreover, TrkA expression was negatively correlated with Ki-67 index and positively correlated with P16 expression. There was a significantly negative correlation between BRAF V600E mutation and abnormal β-catenin expression. Our results demonstrate for the first time that TrkA expression might occur in CP, especially in adult CP patients, and suggest that Cyclin D1 could be used for ACP histological classification in addition to β-catenin and BRAF V600E mutation, while Ki-67 could be used as a marker to predict CP recurrence.